Peak Expiratory Flow Rate Among Rural and Urban Normal School Children in Chattogram, Bangladesh - Zafarullah, AKM; Alam, Md Badrul; Ahmed, Moinuddin; Das, Ashutosh; Alam, Md Shah (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background: Asthma remain the most common chronic inflammatory lung disease in childhood. Asthma management needs lung function assessment. Peak Expiratory Flow Rate (PEFR) is one of the lung function test. PEFR has been used as measure of ventilatory capacity for long mainly because of a simple, less tiring procedure than other lung function test. It is easy to use, inexpensive, portable, reliable can be used by patients, parents, home & clinic. There is no national nomogram on PEFR in Bangladesh. We always use the nomogram of other countries for diagnosis, management of Asthma. This study was taken to establish what is the normal pattern of PEFR in Bangladeshi children of rural and urban area and to construct nomogram of PEFR in healthy Bangladeshi children. Materials and methods : It is a cross sectional study conducted in different 6 schools (Urban & rural) in Chattogram District of both sexes (5-15 yrs old) in equal proportion of child. Study period was from April 2009 to November 2009 under supervision of Pediatrics Department of Chattogram Medical College. Sample was selected by non-probability technique. Data were collected by pretested questionnaire including exclusion criteria. Results: A total of 1424 healthy school children (Age 5-15 yrs) of equal sexes of both rural and urban school were included during study. The best of three PEFR of boys ranged from 90 to 750 I/min (Mean 291 I/min, SD 143) and in case of girls ranged from 80 to 540 (L/min (mean 236 L/min, SD 94.38). The positive correlation of PEFR with various anthrometric parameters specially height and observed difference with boys and girls. The most significant correlation was observed PEFR with height and also found different value of PEFR between rural and urban children. Conclusion : This study concluded that there is significant difference of PEFR between Bangladeshi boys and girls (5-15 yrs). Height is the best predictor of PEFR value than any other anthrometric parameters PEFR value of Bangladeshi Girls is lower than that of Boys and significant difference between PEFR values among urban & rural Bangladeshi children. Chatt Maa Shi Hosp Med Coll J; Vol.18 (1); Jan 2019; Page 18-22